Integration of renewable energy systems in buildings in the line of sustainable construction and energetic efficiency - Marujo, R. (2010)
Being Portugal an extremely active country on the renewable energy area, one of technology niches experiencing a growing interest from investors and population in general are domestic micro-generation systems, especially when integrated in a building’s architecture. As a response to the expectations developed among domestic end-users of distributed renewablebased micro-generation systems, by the end of 2007, the Portuguese government published new legislation to regulate and clarify terms and tariffs for the installation of these small systems. To fulfill the needs of these users - essentially domestic and small and medium companies - INETI initiated the development of tools to characterize the wind resource in urban areas, the wind technological solutions adapted to urban environment – e.g. T.Urban small wind turbine - and tools to assess the viability of the micro-generation systems installation in buildings. This work presents and analyses scenarios for building energetic sustainability, by using a wind (SWT) system, a photovoltaic (PV) system and sizing a hybrid system (SWT+ PV) in a domestic building. Economic and energetic issues of the new legislation are presented and discussed. The results obtained demonstrate that it is very advantageous to become a microproducer in Portugal, if the region of interest is suitable for wind energy exploitation.